(untitled) (Studia Prawnicze / The Legal Studies, 2023)
W pracy zostaje opisany problem przedmiotu własności społecznej w kontekście regulacji prawa cywilnego. Autor artykułu przedstawia rozwiązania prawne zawarte w projektach kodeksu cywilnego z lat 1954 r., 1955 r. oraz lat 60-tych XX wieku. Opisuje szczegółowo klasyfikacje środków trwałych na podstawie uchwały nr 534 Rady Ministrów z dn. 13 grudnia 1961 r w sprawie amortyzacji środków trwałych. Wskazuje, że wyodrębnienie tych środków bazuje głównie na kryteriach ekonomicznych. Ponadto, autor przedstawia zakres ochrony prawnej rzeczy ruchomych stanowiących własność państwową w świetle przepisów kodeksu cywilnego tj. artykułów 171 oraz 223 § 3 k.c. The paper describes the problem of the subject of social property in the context of civil law regulation. The author of this article presents the legal solutions contained in the 1954, 1955 and 1960s drafts of the Civil Code. He describes in detail the classifications of fixed assets on the basis of Resolution No. 534 of the Council of Ministers of 13 December 1961 on depreciation of fixed assets. He points out that the separation of these measures is mainly based on economic criteria. In addition, the author presents the scope of legal protection of movables constituting state property in the light of the provisions of the Civil Code, i.e. Articles 171 and 223 § 3 of the Civil Code.